PENERAPAN PEMBELAJARAN CULTURALLY RESPONSIVE TEACHING BERBANTU MEDIA ULAR TANGGA UNTUK MENINGKATKAN PEMAHAMAN KOGNITIF SISWA - Mutiara Nirwana, Elok; Listiyani, Ivayuni; Nurmaningsih, Eka Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the diversity of cultures, ethnicities and habits of students in this era of globalization which makes many students have many characters and habits in the present. Many also forget local culture because they often use foreign products so that they do not understand the culture of Indonesian products. This study aims to improve students' cognitive understanding using the culturally responsive teaching (CRT) model assisted by snake and ladder game media in the subject of science on Indonesian product material. The subjects in this study were grade V students with a total of 6 students. The data collection tools used were assessment rubrics and evaluation sheets. The results of the study showed that the average value and cognitive understanding of students before the action was 65.83 only in the sufficient category, in cycle I it increased to 77.5 in the good category and in cycle II it increased significantly to 88.33 in the very good category.